Analysis Of Pv Wind Battery Hybrid Power System (Pwbhps) Using Simple Zone Probabilities (Szp) Method For Household In Malaysia - Suriadi, Suriadi (2016)
The development of Hybrid Power System (HPS) had contributed to the utilization of Renewable Energy (RE) power as an alternative power source. The total usage of RE is normally depend on the type of load and the system design. This thesis proposed the PV Wind Battery Hybrid Power System (PWBHPS) that will utilize energy from solar and wind as a main source. The hybrid configuration that was modeled consists of PV, Wind and Battery and it was connected in parallel with the grid. A new technique which is known as Simple Zone Probabilities (SZP) had been implemented to optimize the overall system performance. The load profile which is employed in this study has a peak load during sun hours (e.g. at noon). The collected daily data of wind and solar was arranged through Microsoft Excel to determine the total output power for zoning probabilities. The suitable locations in Malaysia were selected as a base study due to data availability and the potential to install the hybrid system. It has been recorded that solar radiation intensity and average wind speed in Malaysia are found to be 5.5 kWh/m2/day and 3m/s, respectively. The practical results are based on 1.4 kW photovoltaic, 2 kW wind turbine and 10 batteries of 18Ah where the average power that can be generated is nearly 30% of the total system capacity. The results show that the total annual energy maximum generated is 4013 kWh and for 30 years life span is expected to be 123090 kWh. Results from the developed PWBHPS show the average output power using SZP can supplying a load of 66.65 %, while without SZP of 53.6%at the selected locations. The results show that the highest potential energy hybrid was obtained at Mersing, Johor (100%). This thesis also describes that the PWBHPS can be used interchangeably automatically with the grid in serving the load. The economic analysis shows that the initial cost of the 2 kW PWBHPS is RM 20,951 and the payback period is calculated to be nearly 19 years, where the cost is 27 cents per kWh.